Managing the high-production herd. V. challenges of the 90's - Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
The decade of the 1980s was a transition period for the Dairy Industry in the United States. The decade began with a large milk surplus and low prices and ended with milk shortages and record high prices. The dairy industry experienced drastic governmental action through the milk set-aside and whole herd buy-out programs instituted to reduce the milk surplus and the establishment of the National Dairy Board accompanied by a check-off program to fund advertising and research. The decade ended with a butter surplus and moves by marketing agencies to lower or drop premiums for fat and install premiums for milk protein or solids-not-fat.
The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: High-production herd; Dairy; Challenges